Ethical leadership and workplace behavior in the education sector: The implications of employees' ethical work behavior - Guo, Fengrui; Xue, Zhongyi; He, Jiaxu; Yasmin, Fakhra (Frontiers in Psychology, 2023)
The study aimed to examine the effect of ethical leadership on employees' ethical work behavior. Furthermore, this study examined the mediating role of organizational commitment in the relationship between ethical leadership and employees' ethical work behavior. This study was conducted in a public-sector educational organization, and 500 questionnaires were distributed among targeted employees. Out of these, 400 valid responses were received from individuals working in the education sector in China. The findings showed a positive and significant impact of ethical leadership on employees' ethical work behavior. We found that organizational commitment also significantly mediates the relationship between ethical leadership and employees' ethical work behavior. The practical implications of the current study are useful for all organizations in the public sector. As ethical leadership is positively related to employees' work behavior, we recommend that organizations should develop and conduct such training programs to promote ethical work behavior. Leaders with a strong sense of ethics should be hired to encourage ethical work behavior within the organization. Furthermore, organizations can conduct management training programs, seminars, and workshops to encourage such behavior. Ethical behavior can be encouraged among employees by making it a clear requirement of their jobs. To achieve positive results, top management and leadership must educate employees on the value and importance of ethical behavior in the workplace.